2015
DOI: 10.3136/fstr.21.247
|View full text |Cite
|
Sign up to set email alerts
|

Component Analysis of Wasabi Leaves and an Evaluation of their Anti-inflammatory Activity

Abstract: The methanol extracts of wasabi leaves (Wasabia japonicaMatsumura

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Activity‐guided fractionation from the MeOH extract of wasabi leaves obtained from the study by Yoshida et al () was performed. Compound 1 was isolated from the EtOAc extract.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Activity‐guided fractionation from the MeOH extract of wasabi leaves obtained from the study by Yoshida et al () was performed. Compound 1 was isolated from the EtOAc extract.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, wasabi leaves are mostly discarded because they contain little isothiocyanates. However, several studies on the components and functionalities of wasabi leaves have been conducted recently, showing that they contain flavonoids (Hosoya, Yun, & Kunugi, 2005), phenylpropanoids (Hosoya, Yun, & Kunugi, 2008), terpenoids (Yoshida, Hosoya, Inui, Masuda, & Kumazawa, 2015), and carotenoids (Yoshida et al, 2015). Meanwhile, the functional studies revealed that their effects include antioxidant (Hosoya et al, 2008) and anti-inflammatory activities (Yoshida et al, 2015).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, research results suggest other possible uses of this crop in plant protection and in human medicine. Wasabi has a strong antimicrobial (Depree et al, 1999;Delaquis and Mazza, 1995;Khan et al, 2006), anti-inflammatory (Yoshida et al, 2015;Uto et al, 2005) and antibacterial effect (Shin et al, 2004). Many authors recorded positive medicinal effects of Wasabi-extracted substances.…”
Section: Introductionmentioning
confidence: 99%